FORMING A SENSE OF MILITARY PATRIOTISM IN THE EDUCATION OF YOUNG PEOPLE, THE ROLE AND IMPORTANCE OF LEGAL EDUCATION - Akhmadaliyev Muhammedali Gaybillojan Ogli; Abdumuttaliyev Sardorbek Ahadjon ogli; Mominov Azizbek Tojali ogli (Scholar Express Journal, 2022)
In the context of this article, the importance of legal education and upbringing of the military patriotism in the education of our nation's youth is to develop a mentally mature and physically healthy person. The role of national identity and historical memory is considered to educate young people in the spirit of military patriotism, to teach them to love their country, people and family, to learn the great heritage left by our patriotic grandfathers and to become their worthy heirs.
Keywords: Patriotism; military; youth; education